ANALISIS KETERAMPILAN PROSES SAINS MAHASISWA PENDIDIKAN BIOLOGI PADA KEGIATAN PRAKTIKUM MIKROBIOLOGI - Anita H (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
This research is a type of qualitative research, aiming to assess the level of science process skills possessed by students majoring in biology education at the Higher Education Teacher Training Institute, Turatea Jeneponto College Foundation. The research method used is observation of the implementation of microbiology practicum activities carried out by Biology Education Department Students for the 2020/2021 Academic Year as many as 17 students using microbiology practicum guides based on science process skills that have been developed previously and assessment of practicum reports by each practitioner as well as scientific process skill observation sheet that has been validated. The analysis technique used includes the data collection stage using an assessment format for student trainees which contains 8 skill items, namely observing, classifying, interpreting, predicting, asking questions, conducting experiments, hypotheses and communicating experimental results. The next stage is data reduction, data display using descriptive statistics in the form of tables, triangulation and drawing conclusions. The results of the study provide an illustration that in the implementation of microbiology practicum activities, science process skills students of the Department of Biology Education, Higher Education Teacher Training Institute, Turatea Jeneponto College Foundation, on average, show a sufficient category with an average score of 52.50.